Estimation of lifetime survival and predictors of mortality among TB with HIV co-infected children after test and treat strategies launched in Northwest, Ethiopia, 2021; a multicentre historical follow-up study. - Ermias Sisay Chanie; Getnet Asmare Gelaye; Tesfaye Yimer Tadesse; Dejen Getaneh Feleke; Wubet Taklual Admas; Eshetie Molla Alemu; Melkalem Mamoye Azanaw; Sofonyas Abebaw Tiruneh; Alemayehu Digssie Gebremariam; Binyam Minuye Birhane; Wubet Alebachew Bayih; Getachew Aragie (PLoS ONE)
Introduction In resource-limited settings, the mortality rate among tuberculosis and human Immunodeficiency virus co-infected children is higher. However, there is no adequate evidence in Ethiopia in general and in the study area in particular. Hence, this study aims to estimate lifetime survival and predictors of mortality among TB with HIV co-infected children after test and treat strategies launched in Northwest Ethiopia Hospitals, 2021. Methods Institution-based historical follow-up study was conducted in Northwest Ethiopia Hospitals among 227 Tuberculosis and Human Immunodeficiency Virus co-infected children from March 1, 2014, to January 12, 2021. The data were entered into Epi info-7 and then exported to STATA version 14 for analysis. The log-rank test was used to estimate the curve difference of the predictor variables. Bivariable cox-proportional hazard models were employed for each predictor variable. Additionally, those variables having a p-value < 0.25 in bivariate analysis were fitted into a multivariable cox-proportional hazards model. P-value < 0.05 was used to declare significance associated with the dependent variable. Results From a total of 227 TB and HIV co-infected children, 39 died during the follow-up period. The overall mortality rate was 3.7 (95% CI (confidence interval): 2.9-4.7) per 100 person-years with a total of 1063.2-year observations. Cotrimoxazole preventive therapy (CPT) non-users [Adjusted Hazarded Ratio (AHR) = 3.8 (95% CI: 1.64-8.86)], presence of treatment failure [AHR = 3.0 (95% CI: 1.14-78.17)], and Cluster of differentiation 4(CD4) count below threshold [AHR = 2.7 (95% CI: 1.21-6.45)] were significant predictors of mortality. Conclusion In this study, the mortality rate among TB and HIV co-infected children was found to be very high. The risk of mortality among TB and HIV co-infected children was associated with treatment failure, CD4 count below the threshold, and cotrimoxazole preventive therapy non-users. Further research should conduct to assess and improve the quality of ART service in Northwest Ethiopia Hospitals.